1995
DOI: 10.1038/ng0995-52
|View full text |Cite
|
Sign up to set email alerts
|

Peg1/Mest imprinted gene on chromosome 6 identified by cDNA subtraction hybridization

Abstract: Parthenogenesis in the mouse is embryonic lethal partly because of imprinted genes that are expressed only from the paternal genome. In a systematic screen using subtraction hybridization between cDNAs from normal and parthenogenetic embryos, we initially identified two apparently novel imprinted genes, Peg1 and Peg3. Peg1 (paternally expressed gene 1) or Mest, the first imprinted gene found on the mouse chromosome 6, may contribute to the lethality of parthenogenones and of embryos with a maternal duplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
205
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(208 citation statements)
references
References 35 publications
2
205
0
1
Order By: Relevance
“…The imprinted mouse Pegl/M est gene was identified in a systematic screen using subtraction hybridization with cDNAs from parthenogenetic and control embryos (Kaneko-Ishino et al, 1995). Subsequent homology search revealed th at Pegl was identical to the pre viously identified mesoderm-specific cDNA Mest (Sado et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The imprinted mouse Pegl/M est gene was identified in a systematic screen using subtraction hybridization with cDNAs from parthenogenetic and control embryos (Kaneko-Ishino et al, 1995). Subsequent homology search revealed th at Pegl was identical to the pre viously identified mesoderm-specific cDNA Mest (Sado et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, m aternal duplication of the proximal re gion of chromosome 6 is lethal in embryogenesis, possibly because of deficient Pegl/Mest expression. In con trast, paternal duplication of the proximal region of chromosome 6 is viable, suggesting th at the excess gene dosage for Pegl/Mest, or of any other im printed gene in this region, has no detectable influence on development (Cattanach and Beechey, 1990;Beechey and Cattanach, 1995;Kaneko-Ishino et al, 1995). Second, Pérez Jurado et al (1996) determined the parental origin of a deletion found in patients with Williams syndrome, a neurodevelopmental disorder in volving growth retardation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaky expression of the maternal PEG1/MEST gene observed in humans but not in the mouse could be sufficient to avoid embryonic lethality. 20,31 In mice, imprinting and X-inactivation processes are, in general, more strictly regulated than in humans which might explain the more severe problems observed on parent-specific duplications of imprinted regions.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse homologue, Peg1/Mest, is widely expressed during embryonic development, particularly in mesodermal tissues, and in areas of the developing brain. 16 Targeted inactivation of the paternally derived Peg1/Mest allele results in embryonic growth retardation and, significantly, Peg1/Mest deficient females show abnormal maternal behaviour, providing evidence for a role of Peg1/Mest in the regulation of mammalian behaviour. 17 Human PEG1/MEST expression has been shown to be imprinted in all fetal tissues.…”
Section: Introductionmentioning
confidence: 99%